The structure of smoking motivation: The development and initial validation of a smoking motives inventory. - Forrester, Leslie Anne. (University of Ottawa (Canada), 2001)
There has been increasing pressure on all health-related disciplines, including epidemiology to translate research findings into practice. As a result, the need for valid and reliable data has become increasingly important. The primary objective of the present investigation was to develop a clinically relevant and psychometrically sound measure of motivation for the maintenance of smoking behaviour. A balance of clinimetric and psychometric strategies for scale development was employed. Based on a sample of 200 regular daily smokers, the present study revealed that there are three prominent and important factors that motivate smokers to maintain their smoking behaviour. Specifically, our data demonstrated that regular daily smokers are motivated to maintain their smoking behaviour to reduce or eliminate negative emotions, to satisfy their addiction to cigarettes and to obtain pleasure and relaxation. The literature, however, has identified at least seven factors that motivate smokers to maintain their smoking behaviour. Explanations for the discrepancy in the number of smoking motive factors observed are forwarded. Preliminary psychometric evaluation of the Smoking Motives Inventory and two of its subscales, namely Reduction in Negative Affect and Addiction, indicate strong support for the internal consistency reliability of the scale and initial support for its validity, Further work is required to develop the Pleasure and Relaxation factor. Finally, the implications of the findings and directions for future research are presented.
Keywords: Psychology, Behavioral.